Fetal eye ultrasound: Normal anatomy, abnormal findings, and clinical impact - Kagan, Karl-Oliver; Tost, Frank; Heling, Kai-Sven; Hoopmann, Markus; Sonek, Jiri; Chaoui, Rabih (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Until now, ultrasound examination of the fetal eyes has not played an important role in prenatal diagnosis. National and international guidelines are generally confined to documentation of the presence of the orbits and the lenses. However, in recent years, with the advent of high-resolution ultrasound technology and increasing knowledge of prenatal medicine and genetics, careful examination of the fetal eye has enabled the detection of many ocular malformations before birth. This article provides an overview of the anatomy related to the development of the fetal eye and covers the following conditions: hypertelorism, hypotelorism, exophthalmos, microphthalmos, coloboma, cataract, persistent hyperplastic primary vitreous, retinal detachment, dacryocystocele, and septooptic dysplasia, etc. It is designed to illustrate the spectrum of ocular malformations and their appearance on prenatal ultrasound and to discuss their clinical impact and association with various syndromes.Bislang hat die Ultraschalluntersuchung der fetalen Augen in der Pränataldiagnostik keine große Rolle gespielt. Nationale und internationale Leitlinien beschränken sich im Allgemeinen auf die Dokumentation des Vorhandenseins der Augenhöhlen und der Linsen. In den letzten Jahren ermöglichten jedoch die hochauflösenden Ultraschallgeräte und das zunehmende Wissen in der Pränatalmedizin und Genetik die detaillierte pränatale Untersuchung des fetalen Auges. Dadurch lassen sich viele Augenfehlbildungen bereits vor der Geburt erkennen. Dieser Artikel gibt einen Überblick über die sonografische Anatomie des fetalen Auges und dessen vorgeburtliche Entwicklung. Zudem werden folgende Erkrankungen im Detail beleuchtet: Hypertelorismus, Hypotelorismus, Exophthalmie, Mikrophthalmie, Kolobom, Katarakt, persistierender hyperplastischer primärer Glaskörper, Netzhautablösung, Dakryozystozele und septooptische Dysplasie.